The Dinosaurian Ichnofauna of the Lower Cretaceous (Valanginian–Barremian) Broome Sandstone of the Walmadany Area (James Price Point), Dampier Peninsula, Western Australia. Issue 6 (12th December 2016) - Salisbury, Steven W.; Romilio, Anthony; Herne, Matthew C.; Tucker, Ryan T.; Nair, Jay P.
ABSTRACT: Extensive and well-preserved tracksites in the coastally exposed Lower Cretaceous (Valanginian–Barremian) Broome Sandstone of the Dampier Peninsula provide almost the entire fossil record of dinosaurs from the western half of the Australian continent. Tracks near the town of Broome were described in the late 1960s as Megalosauropus broomensis and attributed to a medium-sized theropod trackmaker. Brief reports in the early 1990s suggested the occurrence of at least another nine types of tracks, referable to theropod, sauropod, ornithopod, and thyreophoran trackmakers, at scattered tracksites spread over more than 80 km of coastline north of Broome, potentially representing one of the world's most diverse dinosaurian ichnofaunas. More recently, it has been proposed that this number could be as high as 16 and that the sites are spread over more than 200 km. However, the only substantial research that has been published on these more recent discoveries is a preliminary study of the sauropod tracks and an account of the ways in which the heavy passage of sauropod trackmakers may have shaped the Dampier Peninsula's Early Cretaceous landscape. With the other types of dinosaurian tracks in the Broome Sandstone remaining undescribed, and the full extent and nature of the Dampier Peninsula's dinosaurian tracksites yet to be adequately addressed, the overall scientific significance of the ichnofauna has remained enigmatic. At the request of the area's Goolarabooloo Traditional Custodians, 400+ hours of ichnological survey work was undertaken from 2011 to 2016 on the 25 km stretch of coastline in the Yanijarri–Lurujarri section of the Dampier Peninsula, inclusive of the coastline at Walmadany (James Price Point). Forty-eight discrete dinosaurian tracksites were identified in this area, and thousands of tracks were examined and measured in situ and using three-dimensional photogrammetry. Tracksites were concentrated in three main areas along the coast: Yanijarri in the north, Walmadany in the middle, and Kardilakan–Jajal Buru in the south. Lithofacies analysis revealed 16 repeated facies types that occurred in three distinctive lithofacies associations, indicative of an environmental transgression between the distal fluvial to deltaic portions of a large braid plain, with migrating sand bodies and periodic sheet floods. The main dinosaurian track-bearing horizons seem to have been generated between periodic sheet floods that blanketed the preexisting sand bodies within the braid plain portion of a tidally influenced delta, with much of the original, gently undulating topography now preserved over large expanses of the present day intertidal reef system. Of the tracks examined, 150 could be identified and are assignable to a least eleven and possibly as many as 21 different track types: five different types of theropod tracks, at least six types of sauropod tracks, four types of ornithopod tracks, and six types of thyreophoran tracks. Eleven of these track types can formally be assigned or compared to existing or new ichnotaxa, whereas the remaining ten represent morphotypes that, although distinct, are currently too poorly represented to confidently assign to existing or new ichnotaxa. Among the ichnotaxa that we have recognized, only two ( Megalosauropus broomensis and Wintonopus latomorum ) belong to existing ichnotaxa, and two compare to existing ichnotaxa but display a suite of morphological features suggesting that they may be distinct in their own right and are therefore placed in open nomenclature. Six of the ichnotaxa that we have identified are new: one theropod ichnotaxon, Yangtzepus clarkei, ichnosp. nov.; one sauropod ichnotaxon, Oobardjidama foulkesi, ichnogen. et ichnosp. nov.; two ornithopod ichnotaxa, Wintonopus middletonae, ichnosp. nov., and Walmadanyichnus hunteri, ichnogen. et ichnosp. nov.; and two thyreophoran ichnotaxa, Garbina roeorum, ichnogen. et ichnosp. nov., and Luluichnus mueckei, ichnogen. et ichnosp. nov. The level of diversity of the main track types is comparable across areas where tracksites are concentrated: Kardilakan–Jajal Buru (12), Walmadany (11), and Yanijarri (10). The overall diversity of the dinosaurian ichnofauna of the Broome Sandstone in the Yanijarri–Lurujarri section of the Dampier Peninsula is unparalleled in Australia, and even globally. In addition to being the primary record of non-avian dinosaurs in the western half of Australia, this ichnofauna provides our only detailed glimpse of Australia's dinosaurian fauna during the first half of the Early Cretaceous. It indicates that the general composition of Australia's mid-Cretaceous dinosaurian fauna was already in place by the Valanginian–Barremian. Both sauropods and ornithopods were diverse and abundant, and thyreophorans were the only type of quadrupedal ornithischians. Important aspects of the fauna that are not seen in the Australian mid-Cretaceous body fossil record are the presence of stegosaurians, an overall higher diversity of thyreophorans and theropods, and the presence of large-bodied hadrosauroid-like ornithopods and very large-bodied sauropods. In many respects, these differences suggest a holdover from the Late Jurassic, when the majority of dinosaurian clades had a more cosmopolitan distribution prior to the fragmentation of Pangea. Although the record for the Lower Cretaceous of Gondwana is sparse, a similar mix of taxa occurs in the Barremian–lower Aptian La Amarga Formation of Argentina and the Berriasian–Hauterivian Kirkwood Formation of South Africa. The persistence of this fauna across the Jurassic-Cretaceous boundary in South America, Africa, and Australia might be characteristic of Gondwanan dinosaurian faunas more broadly. It suggests that the extinction event that affected Laurasian dinosaurian faunas across the Jurassic-Cretaceous boundary may not have been as extreme in Gondwana, and this difference may have foreshadowed the onset of Laurasian-Eurogondwanan provincialism. The disappearance of stegosaurians and the apparent drop in diversity of theropods by the mid-Cretaceous suggests that, similar to South America, Australia passed through a period of faunal turnover between the Valanginian and Aptian. SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Salisbury, S. W., A. Romilio, M. C. Herne, R. T. Tucker, and J. P. Nair. 2017. The dinosaurian ichnofauna of the Lower Cretaceous (Valanginian–Barremian) Broome Sandstone of the Walmadany area (James Price Point), Dampier Peninsula, Western Australia. Society of Vertebrate Paleontology Memoir 16. Journal of Vertebrate Paleontology 36(6, Supplement). DOI: 10.1080/02724634.2016.1269539.